Corrected speciation and gyromitrin content of false morels linked to ALS patients with mostly slow-acetylator phenotypes - Emmeline Lagrange; Marie-Anne Loriot; Nirmal K. Chaudhary; Pam Schultz; Alden C. Dirks; Claire Guissart; Timothy Y. James; Jean Paul Vernoux; William Camu; Ashootosh Tripathi; Peter S. Spencer (eNeurologicalSci)
A case-control study of sporadic amyotrophic lateral sclerosis (ALS) in a mountainous village in the French Alps discovered an association of cases with a history of eating wild fungi (false morels) collected locally and initially identified and erroneously reported as Gyromitra gigas. Specialist re-examination of dried specimens of the ALS-associated fungi demonstrated they were members of the G. esculenta group, namely G. venenata and G. esculenta, species that have been reported to contain substantially higher concentrations of gyromitrin than present in G. gigas. Gyromitrin is metabolized to monomethylhydrazine, which is responsible not only for the acute oral toxic and neurotoxic properties of false morels but also has genotoxic potential with proposed mechanistic relevance to the etiology of neurodegenerative disease. Most ALS patients had a slow- or intermediate-acetylator phenotype predicted by N-acetyltransferase-2 (NAT2) genotyping, which would increase the risk for neurotoxic and genotoxic effects of gyromitrin metabolites.